2015
DOI: 10.4238/2015.october.21.19
|View full text |Cite
|
Sign up to set email alerts
|

Association of A-20C polymorphism in the angiotensinogen gene with essential hypertension: a meta-analysis

Abstract: ABSTRACT. The A-20C polymorphism in the angiotensinogen (AGT) gene has been associated with increased risk of essential hyper tension in several studies; however, these studies gave inconsistent results. In this study, we performed a meta-analysis to assess the association between AGT A-20C polymorphism and essential hyper tension. Published literature was retrieved from PubMed. Pooled odd's ratio (OR) with 95% confidence interval (CI) was calculated using fixed-or random-effect models. A total of 10 case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Two main AGT gene polymorphisms due to base substitutions were studied and shown to be associated with a high risk of developing various cardiovascular diseases: M235T, which is the substitution of methionine by threonine at codon 235, and T174M, which is the substitution of threonine by methionine at codon 174 [83]. In addition, other AGT gene polymorphisms have been shown to be linked to hypertension, including G217A (substitution of guanine by adenosine at codon 217) and A20C (substitution of adenosine by cytosine at codon 20) [91,92]. The A20C and G217A genotypes, located in the promoter region of the AGT gene, have been shown to influence AGT transcriptional activity and, therefore, the AGT serum levels [91,92].…”
Section: Agt Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main AGT gene polymorphisms due to base substitutions were studied and shown to be associated with a high risk of developing various cardiovascular diseases: M235T, which is the substitution of methionine by threonine at codon 235, and T174M, which is the substitution of threonine by methionine at codon 174 [83]. In addition, other AGT gene polymorphisms have been shown to be linked to hypertension, including G217A (substitution of guanine by adenosine at codon 217) and A20C (substitution of adenosine by cytosine at codon 20) [91,92]. The A20C and G217A genotypes, located in the promoter region of the AGT gene, have been shown to influence AGT transcriptional activity and, therefore, the AGT serum levels [91,92].…”
Section: Agt Polymorphismmentioning
confidence: 99%
“…In addition, other AGT gene polymorphisms have been shown to be linked to hypertension, including G217A (substitution of guanine by adenosine at codon 217) and A20C (substitution of adenosine by cytosine at codon 20) [91,92]. The A20C and G217A genotypes, located in the promoter region of the AGT gene, have been shown to influence AGT transcriptional activity and, therefore, the AGT serum levels [91,92]. It has also been reported that the M235T polymorphism is related to increased AGT levels in serum [57,81].…”
Section: Agt Polymorphismmentioning
confidence: 99%
“…Wang, 2013). In addition, some other AGT gene polymorphisms including G217A and A20C are linked to hypertension (R. Zeng, Wang, Fang, Zhuang, & Fan, 2015). All these studies have provided the potential insights that genetic variation of AGT can contribute to various cardiovascular diseases.…”
Section: Agt Gene Polymorphism and Cardiovascular Diseasesmentioning
confidence: 99%
“…Multiple meta‐analysis have reported that AGT M235T is associated with heart failure (Imen et al, 2015; Jiang, He, & Yang, 2014), MI (Liang et al, 2013; Raygan, Karimian, Rezaeian, Bahmani, & Behjati, 2016; Sui & Gao, 2013), cardiomyopathy (Rani et al, 2017; J. L. Yao et al, 2015), and atrial fibrillation (H. Wang et al, 2015) while AGT T174M is connected to the high risk of MI (Hu, Wang, Pang, & Wang, 2015), hypertension (Liao et al, 2014), and atherosclerosis (W. Z. Wang, 2013). In addition, some other AGT gene polymorphisms including G217A and A20C are linked to hypertension (R. Yao et al, 2015; Zeng, Wang, Fang, Zhuang, & Fan, 2015). All these studies have provided the potential insights that genetic variation of AGT can contribute to various cardiovascular diseases.…”
Section: The Emerging Roles Of Agt In Cardiovascular Diseasesmentioning
confidence: 99%
“… 12 AGT is converted to angiotensin I by renin, and subsequently into angiotensin II by ACE. 13 ACE plays an important role in the regulation of systemic and renal vascular circulation by converting angiotensin I into vasoconstrictor molecule angiotensin II. 14 Higher levels of renin activity and ACE activity during the course of diabetes result in an excess of angiotensin II in the eye, abnormally constricted retinal arterioles, elevated local intravascular blood pressure, reduced retinal blood flow, increased permeability of retinal blood vessels, and ocular neovascularization.…”
Section: Introductionmentioning
confidence: 99%